Broadband visible luminescence in tin fluorophosphate glasses with ultra-low glass transition temperature. Issue 9 (29th January 2018) - Wang, Yajie; Yu, Yue; Zou, Ya; Zhang, Liyan; Hu, Lili; Chen, Danping
Abstract : White light is generated by appropriately altering the SnO/SnF2 molar ratios in the SnF2 –SnO–P2 O5 glass without active ions. Abstract : The structure of tin fluorophosphate glasses and their low melting point properties have attracted a great deal of attention recently, but their own luminescent features have not been well studied. Photoluminescence properties of ultra-low glass transition temperature (<200 °C) tin fluorophosphate glasses with varying SnO/SnF2 molar ratios at room temperature have been investigated in the present study. Broad photoluminescence in the range from 400 nm to 700 nm, originating from the S1 –S0 and T1 –S0 transitions of Sn 2+ with the ultra-high concentration (70 mol%), was obtained. And the SnF2 –SnO–P2 O5 glasses exhibited a fast decay lifetime of 2 ns. Both wavelengths of the excitation peak and emission peak depend on the local structure of Sn 2+, which is influenced by different SnO/SnF2 molar ratios. White light can be generated by appropriately altering the SnO/SnF2 molar ratios in the SnF2 –SnO–P2 O5 glasses. The ultra-low glass transition temperature SnF2 –SnO–P2 O5 glasses without rare earth elements are a possible candidate for future high white light emission.